Adult literacy program in the Division of Tarlac - Paez, Francisca B. 1921- (s.n.], 1969)
The study looked into the present status of the adult literacy program in the Division of Tarlac as sponsored by the Bureau of Public Schools. Findings of the study may serve as a guidance for the making of further studies on the modification of a more functional adult literacy program.